2021
DOI: 10.3390/metabo11090605
|View full text |Cite
|
Sign up to set email alerts
|

Sound Stimulation Can Affect Saccharomyces cerevisiae Growth and Production of Volatile Metabolites in Liquid Medium

Abstract: The biological effect of sound on microorganisms has been a field of interest for many years, with studies mostly focusing on ultrasonic and infrasonic vibrations. In the audible range (20 Hz to 20 kHz), sound has been shown to both increase colony formation and disrupt microbial growth, depending upon the organism and frequency of sound used. In the brewer’s yeast Saccharomyces cerevisiae, sound has been shown to significantly alter growth, increase alcohol production, and affect the metabolite profile. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…The application of various sound intensities and frequencies has previously been shown to enhance the growth rates of S . cerevisiae [ 3 , 4 , 5 , 6 , 9 ], bacterial species [ 5 , 8 , 10 , 11 , 12 , 13 ], algae species [ 14 , 15 ], and plant species [ 16 , 17 , 18 ] compared to control experiments. However, in the current study, the growth rate was not calculated, and rather the number of yeast cells in suspension was reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The application of various sound intensities and frequencies has previously been shown to enhance the growth rates of S . cerevisiae [ 3 , 4 , 5 , 6 , 9 ], bacterial species [ 5 , 8 , 10 , 11 , 12 , 13 ], algae species [ 14 , 15 ], and plant species [ 16 , 17 , 18 ] compared to control experiments. However, in the current study, the growth rate was not calculated, and rather the number of yeast cells in suspension was reported.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has also been reported that hydrostatic pressure, and the amount of nitrogen and glucose in wort can alter ester synthesis [ 30 , 31 ]. The application of high (10 kHz, 90 dB @ 20 µPa) and low (100 Hz, 90 dB @ 20 µPa) audible sound to yeast significantly decreased the production of ethyl octanoate compared to the silence control [ 6 ]. Therefore, it is also possible that the changes in cell numbers in suspension and/or glucose utilization may underlie the differences in the observed levels of esters in our ferments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations